Hernagine type of Aporphine Alkaloids from Alseodaphne perakensis - Md Nazimuddin Mahfuzah, Husna Hasnan Muhammad Hafiz, Ahmad Kartini, Awang Khalijah, Nafiah Mohd Azlan, (N/A, 2014)
Hernagine type of Aporphine Alkaloids from Alseodaphne perakensis by Md Nazimuddin Mahfuzah, Husna Hasnan Muhammad Hafiz, Ahmad Kartini, Awang Khalijah, Nafiah Mohd Azlan,